Taxonomy of European Damaeidae (Acari: Oribatida) I. Kunstidamaeus Miko, 2006, with comments on Damaeus sensu lato - Miko, Ladislav; Mourek, Jan (Zootaxa, 2008)
The diagnosis of the genus Kunstidamaeus Miko, 2006 is given and a new generic concept within Damaeus sensu lato is proposed. Epidamaeus, Kunstidamaeus and Spatiodamaeus are given generic status, whereas Adamaeus, Paradamaeus and the nominal subgenus Damaeus s. stricto are considered to be subgenera of the genus Damaeus. The type species K. lengersdorfi (Willmann, 1932) including the immature stases is redescribed and its geographic distribution and ecology is discussed. The neotype of K. lengersdorfi is designated. Together with the type species, the genus Kunstidamaeus includes seven known European species: K. tenuipes (Michael, 1885), K. tecticola (Michael, 1888), K. nivalis (Kulczynski, 1902), K. nidicola (Willmann, 1936), K. diversipilis (Willmann, 1951), K. granulatus (Willmann, 1951), and K. longisetosus (Willmann, 1953).